2021
DOI: 10.1111/vop.12931
|View full text |Cite
|
Sign up to set email alerts
|

Topical bevacizumab for the treatment of corneal vascularization in dogs: A case series

Abstract: Objective To evaluate the effect and safety of topical anti‐human vascular endothelial growth factor bevacizumab in dogs with persistent corneal vascularization. Animals studied Prospective case series of 15 adult dogs (20 eyes). Procedures Dogs received 0.25% bevacizumab eye drops BID for 28 days. Follow‐ups were scheduled 28 days and 6–7 months after treatment start. Macroscopic findings were scored for conjunctival hyperemia, chemosis, ocular discharge, corneal edema, vascularization, and pigmentation. Vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 60 publications
(119 reference statements)
0
9
0
Order By: Relevance
“…Topical bevacizumab 0.25 % q12h in one eye over 28 days was a safe treatment in healthy beagles [17] and adverse effects appeared unlikely in diseased dogs [10]. In the present case, only subconjunctival [18] or intrastromal applications were considered effective since the corneal epithelium was intact.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Topical bevacizumab 0.25 % q12h in one eye over 28 days was a safe treatment in healthy beagles [17] and adverse effects appeared unlikely in diseased dogs [10]. In the present case, only subconjunctival [18] or intrastromal applications were considered effective since the corneal epithelium was intact.…”
Section: Discussionmentioning
confidence: 68%
“…To achieve the treatment goal of an avascular, immune-privileged cornea, neovascularization can be addressed by a targeted anti-VEGF therapy. While previous publications investigated anti-VEGF-A in human oncology, reports in veterinary literature are sparse [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 In animal models with corneal neovascularization, the levels of expression of vascular endothelial growth factor and its receptors have been found to be increased. 12,13 Research studies conducted on humans have also demonstrated that the expression of vascular endothelial growth factor and its receptors is higher in the cornea of the patients with corneal neovascularization, regardless of the cause. 14 Additionally, the blockage of vascular endothelial growth factor at the level of both mRNA and protein synthesis, has resulted in reduction in corneal neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“… 24 To facilitate the interpretation, only an average score was reported. When the wounds showed no fluorescein uptake, the appearance of the cornea was evaluated clinically to check for the presence of scarring, pigmentation, and vascularization as previously described 25–27 …”
Section: Methodsmentioning
confidence: 99%